Homeless and Beggar Handling Policy in Semarang: Problems and Challenges - Nugraha, Terry Rangga (Universitas Negeri Semarang, 2022)
The study is intended to analyze problems of welfare in Indonesian society, especially in the city of Semarang. The results of the study, Semarang City itself has the Regulation No. 5 of 2014 on the Handling of Street Children and Beggars, Tramps, and Displaced Persons (Pengemis, Gelandangan, dan Orang Terlantar, or PGOT) designed Parliament with the Mayor for the usefulness of ordering Semarang city free of street children, beggars, Displaced Persons, thus the Satpol PP Unit in disciplining beggars, vagrants, and displaced persons and street children rely on the local regulation in performing their duties. After the raids and controls carried out by the Satpol PP of Semarang City, then followed up by the Central Java Provincial Social Office to rehabilitate the beggars, the tramps, and the landed people not to return to the road, thus creating a comfortable urban area. Semarang City Government may be able to apply a theory of Socialist Furnace in realizing Semarang City which is comfortable, the furnace theory includes education stove, economic furnace, and health stove. The theory can be used as a reference in dealing with the problems mentioned above.